Análisis de las estrategias publicitarias utilizadas por el AITEC tecnológico Almirante Illingworth en los alumnos de tercer año de bachillerato de la ANAI, academia naval Almirante Illingworth periodo lectivo 2016-2017 - Muñoz Zamora, Alexandra María (2016)
The present researching work has the goal to analyze which are advertising strategies used by AITEC to achieve what the positioning in students of third baccalaureate of ANAI high school. In the path that AITEC has, it can be seen that the technology in question has not developed proper positioning of its right image positioning in students of third baccalaureate of ANAI high school, because it lacks proper communication and advertising strategy that encourages the student to remain in the institution…..